Совершенствование технологического процесса вертикального перемещения грузов краном на основе повышения степени его автоматизации - Климченкова, Н. В.; Кириченко, Т. В.; Кутковой, И. П. (Eastern-European Journal of Enterprise Technologies, 2009)
The increase of the productivity of loadings cranes is carried out due to automation of technological process of moving of loads. On these initial parameters of concrete load and way of motion control program controls flowing of every technological operation